2011
DOI: 10.1038/jcbfm.2011.179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender on Gene Expression in the Blood of Ischemic Stroke Patients

Abstract: This study examined the effects of gender on RNA expression after ischemic stroke (IS). RNA obtained from blood of IS patients (n = 51; 153 samples at p3, 5, and 24 hours) and from matched controls (n = 52) were processed on Affymetrix microarrays. Analyses of covariance for stroke versus control samples were performed separately for both genders and the regulated genes for females compared with males. In all, 242, 227, and 338 male-specific genes were regulated at p3, 5, and 24 hours after IS, respectively, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 39 publications
6
41
0
Order By: Relevance
“…obs. Robert Meller RM), which agrees with reports of gene expression differences following stroke between males and females 28, 29. These preliminary data show the clear need for further studies to better understand both racial and sex‐associated differences in response to stroke.…”
Section: Discussionsupporting
confidence: 85%
“…obs. Robert Meller RM), which agrees with reports of gene expression differences following stroke between males and females 28, 29. These preliminary data show the clear need for further studies to better understand both racial and sex‐associated differences in response to stroke.…”
Section: Discussionsupporting
confidence: 85%
“…12 Recent studies further showed that there are sex-associated changes in gene expressions in the blood obtained from patients with ischemic stroke 13 and in microRNA expression in mice with cerebral ischemia. 14 These sex-associated responses to cerebral ischemia may partly contribute to sex difference in stroke severity.…”
Section: Article In Pressmentioning
confidence: 98%
“…Results from Oh et al[21] were published after this study commenced. In several other microarray studies the utility of gene expression was investigated: for the evaluation of the risk of hemorrhagic transformation[23], defining stroke etiology[24-26] and in studying gender related gene expression changes in stroke patients[27,28]. …”
Section: Discussionmentioning
confidence: 99%